Myocardial infarction and individual nonsteroidal anti‐inflammatory drugs meta‐analysis of observational studies. (25th April 2013) - Varas‐Lorenzo, Cristina; Riera‐Guardia, Nuria; Calingaert, Brian; Castellsague, Jordi; Salvo, Francesco; Nicotra, Federica; Sturkenboom, Miriam; Perez‐Gutthann, Susana
ABSTRACT Objective To conduct a systematic review of observational studies on the risk of acute myocardial infarction (AMI) with use of individual nonsteroidal anti‐inflammatory drugs (NSAIDs). Methods A search of Medline (PubMed) for observational studies published from 1990 to 2011 identified 3829 articles; 31 reported relative risk (RR) of AMI with use of individual NSAIDs versus nonuse of NSAIDs. Information abstracted in a standardized form from 25 publications was used for the meta‐analysis on 18 independent study populations. Results Random‐effects RR (95% confidence interval (CI)) was lowest for naproxen 1.06 (0.94–1.20), followed by celecoxib 1.12 (1.00–1.24), ibuprofen 1.14 (0.98–1.31), meloxicam 1.25 (1.04–1.49), rofecoxib 1.34 (1.22–1.48), diclofenac 1.38 (1.26–1.52), indometacin 1.40 (1.21–1.62), etodolac 1.55 (1.16–2.06), and etoricoxib 1.97 (1.35–2.89). Heterogeneity between studies was present. For new users, RRs (95% CIs) were for naproxen, 0.85 (0.73–1.00); ibuprofen, 1.20 (0.97–1.48); celecoxib, 1.23 (1.00–1.52); diclofenac, 1.41 (1.08–1.86); and rofecoxib, 1.43 (1.21–1.66). Except for naproxen, higher risk was generally associated with higher doses, as defined in each study, overall and in patients with prior coronary heart disease. Low and high doses of diclofenac and rofecoxib were associated with high risk of AMI, with dose–response relationship for rofecoxib. In patients with prior coronary heart disease, except for naproxen, duration of use ≤3 months was associated with an increased risk of AMI. Conclusions Most frequently NSAIDs used in clinical practice, except naproxen, are associated with an increased risk of AMI at high doses or in persons with diagnosed coronary heart disease. For diclofenac and rofecoxib, the risk was increased at low and high doses. Copyright © 2013 John Wiley & Sons, Ltd.